Prática de pilates por idosas: vivências de felicidade, saúde e bem-estar em pauta - Oliveira, Talia Castilhos de (2017)
Pilates Method seeks to provide quality in life and general well-being, by postural optimization, mobility, balance and agility, through muscle toning, increased flexibility and body elasticity. Thus, the aim of this study was to identify the contributions of Pilates method as a promoter of health / happiness / general well-being, with 15 elderly women, participants in Pilates workshops, at a Reference Center for Elderly Care of the University of Passo Fundo , using a semi-structured interview. The information was synthesized into categories, according to Bardin’s content analysis, and connected to the literature. From the results four categories emerged: the physical well-being and the psychic well-being, the living and the coexistence, and the happiness. From the positive effects reported by the elderly with regular practice of Pilates, body aches reduction, postural balance improvement, body and mind balance, memory optimization, self care, autonomy, protagonism, acquaintanceship and happiness have occured. It is inferred that Pilates Method assists in the successful aging of the elderly who regularly practice it.